2022
DOI: 10.1017/s1047951122000439
|View full text |Cite
|
Sign up to set email alerts
|

The effects of music intervention on anxiety and stress responses in adults with CHD undergoing cardiac catheterisation

Abstract: Introduction: This study evaluated the effect of music intervention on the anxiety and stress responses of patients who underwent an interventional cardiac catheterisation. Methods: The study design was a pre- and post-test randomised controlled trial that included 94 patients who underwent a transcatheter atrial septal defect closure. Patients were allocated to receive either music intervention (n = 47) or usual care (n = 47) during the interventional cardiac catheterisation. Music inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Moreover, a randomized clinical trial in South Korea evaluated the effect of a music intervention on the anxiety and stress responses of patients undergoing cardiac catheterization using the State Anxiety Inventory (SAI) and the numerical anxiety rating scale (NARS). The study revealed that the music intervention effectively reduced anxiety and stress responses that precede cardiac catheterization, emphasizing the importance of this type of intervention for anxiety management (Moon et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a randomized clinical trial in South Korea evaluated the effect of a music intervention on the anxiety and stress responses of patients undergoing cardiac catheterization using the State Anxiety Inventory (SAI) and the numerical anxiety rating scale (NARS). The study revealed that the music intervention effectively reduced anxiety and stress responses that precede cardiac catheterization, emphasizing the importance of this type of intervention for anxiety management (Moon et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…(20,21) Researchers assessed the effect of musical intervention on anxiety and stress responses in patients undergoing cardiac catheterization. (53) RCT that assessed the effectiveness of the musical intervention in terms of anxiety, cortisol level and HR variability showed evidence of a reduction in anxiety and stress response of the musical intervention preceding cardiac catheterization, indicating that this intervention should be considered. Anxiety was also assessed by STAI (F = 31.42, p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety was also assessed by STAI (F = 31.42, p < 0.001). (53) Literature review showed different psychological preparation strategies and relaxation techniques that have been tested to reduce anxiety, stabilize physiological parameters and reduce pain intensity. (25) Education regarding the procedure was observed in 11 of the 29 studies analyzed and was effective in reducing anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative surgery not only requires a greater amount of anesthetic, but also results in increased catecholamine release causing tachycardia, hypertension, and cardiac arrhythmias. Moreover, anxiety before surgery is related to recovery and pain levels after surgery (4,5). A high prevalence of stress and anxiety has been observed in pregnant women (6).…”
Section: Introductionmentioning
confidence: 99%